Accelerated diffusion-weighted imaging for lymph node assessment in the pelvis applying simultaneous multislice acquisition: A healthy volunteer study. Issue 32 (August 2018) - Ciritsis, Alexander; Rossi, Cristina; Marcon, Magda; Van, Valerie Doan Phi; Boss, Andreas
Abstract : Abstract: To evaluate the feasibility of accelerated simultaneous multislice diffusion weighted sequences (SMS-DWI) for lymph node detection in the abdominopelvic region. Sequences were evaluated regarding the number and depiction of lymph nodes detected with SMS-DWI compared with conventional diffusion weighted sequences, the most suitable SMS- acceleration factor, signal-to-noise ratio (SNR), and the overall acquisition time (TA). Eight healthy volunteers (4 men, 4 women; age range 21–39 years; median age 25 years) were examined in the pelvic region at 3T using a conventional DWI sequence and a SMS DWI sequence with different acceleration factors (AF: 2–3). Moreover, a SMS DWI sequence with AF 3 and higher slice resolution was applied. For morphological correlation of the lymph nodes and as a reference standard, an isotropic 3-dimensional T2-weighted fast-spin-echo sequence with high sampling efficiency (SPACE) was acquired. Two radiologists reviewed each DWI sequence and assessed the number of lymph nodes and the overall image quality. For each DWI sequence, SNR, SNR efficiency per time, contrast to noise (CNR), and ADC values were calculated. Values were statistically compared using a Wilcoxon test ( P < .05). Overall, scan time of SMS-DWI with AF2 (AF3) decreased by 46.9% (57.2%) with respect to the conventional DWI. Compared with the SPACE sequence, the detection rate was 89.6% for conventional DWI, 69.4% for SMS-DWI with AF2, and 59.9% for SMS-DWI with AF3. The highly resolved SMS-DWI with AF3 leads to a scan time reduction of 46.9% and detection rate of 83.0%. SNR and CNR were lower in the accelerated sequences (up to 51.0%, P < .001) as compared with the conventional DWI. SNR efficiency decreased to 19.3% for AF2 and to 31.3% for AF3. In the highly resolved dataset, an SNR efficiency reduction of 51.2% was found. This study showed that lymph node detection in the abdominopelvic region with accelerated SMS-DWI sequences is feasible whereby an AF of 2 represents the best compromise between image quality, SNR, CNR, TA, and detection rate.